A Role for Syntaxin 3 in the secretion of IL-6 from Dendritic Cells following activation of Toll-like Receptors - Collins, Laura E.; DeCourcey, Joseph; Rochfort, Keith D.; Kristek, Maja; Loscher, Christine E. (Frontiers in Immunology, 2015)
The role of dendritic cells (DCs) in directing the immune response is due in part to their capacity to produce a range of cytokines. Importantly, DCs are a source of cytokines which can promote T cell survival and T helper cell differentiation. While it has become evident that soluble-N-ethylmaleimide-sensitive-factor accessory-protein receptors (SNARE) are involved in membrane fusion and ultimately cytokine release, little is known about which members of this family facilitate the secretion of specific cytokines from DCs. We profiled mRNA of eighteen SNARE proteins in DCs in response to activation with a panel of three toll-receptor (TLR) ligands and show differential expression of SNAREs in response to their stimulus and subsequent secretion patterns. Of interest, STX3 mRNA was up-regulated in response to TLR4 and TLR7 activation but not TLR2 activation. This correlated with secretion of IL-6 and MIP-1α. Abolishment of STX3 from DCs by RNAi resulted in the attenuation of IL-6 levels and to some extent MIP-1α levels. Analysis of subcellular location of STX3 by confocal microscopy showed translocation of STX3 to the cell membrane only in DCs secreting IL-6 or MIP-1α, indicating a role for STX3 in trafficking of these immune mediators. Given the role of IL-6 in Th17 differentiation, these findings suggest the potential of STX3 as therapeutic target in inflammatory disease.